Curbing the Global Economic Downturn : Southeast Asian Macroeconomic Policy - Aekapol Chongvilaivan; Institute of Southeast Asian Studies (Singapore : Institute of Southeast Asian Studies, 2010)
Southeast Asia witnessed a wide array of policy actions at the regional and international levels to unravel the ripple effects of the global economic downturn and to set a stage for a long-term recovery. Yet the quest for regional and global solutions has been hampered critically by the complication of individual economies and the diverse levels of economic development. The objective of this book is to examine in-depth region-specific research on how macroeconomic tools are at work in the Southeast Asian economies.
Macroeconomic impacts of a financial crisis / Iwan J. Azis and Yuri Mansury -- Capital inflow reversals, current account adjustments, and macroeconomic performance / Gan Wee Beng and Soon Lee Ying -- Supply-side causes of macroeconomic fluctuations in small open economy / Choy Keen Meng -- Effectiveness of fiscal stimuli / Tsangyao Chang, Wen Rong Liu, and Herry Thompson -- Public debt sustainability and its macroeconomic impacts / Anthony J. Makin -- Gains from intra- and inter-regional trade and economic co-operation / Sasatra Sudsawasd and Prasopchoke Mongsawad -- From economic reform to closer economic ties / Jenny D. Balboa, Erlinda M. Medalla, and Josef T. Yap -- Macroeconomic surveillance and financial co-operation / Warapot Manupipatpong.
Title from publisher's bibliographic system (viewed on 24 Nov 2015).
Keywords: Macroeconomics; Southeast Asia -- Economic policy